Experimental analysis on grain growth kinetics of SS316l austenitic stainless steel / Muhd Faiz Mat ... [et al.] - Mat, Muhd Faiz; Manurun, Yupiter H. P.; Busari, Yusuf Olanrewaju; Adenan, Mohd Shahriman; Sulaiman, Mohd Shahar; Muhammad, Norasiah; Graf, Marcel (Universiti Teknologi MARA, 2021)
This paper presents an investigation of austenitic stainless steel grain growth kinetics of SS316L under different heating temperature ranges and holding times. The main variables such as apparent activation energy (Q), rate constant (K), and kinetic exponent (n) were analyzed to understand the grain growth kinetics in austenitic stainless steel. The empirical procedure was developed leading to the obtainment of variables that could define the grain growth kinetics based on different temperature ranges. The heat treatment process was isothermally held using quenching and deformations dilatometer at a temperature ranging from 900 °C to 1200 °C and holding times between 30 s to 240 s. The kinetic rates were estimated using an empirical equation. Based on the observations obtained by using optical microscopy. The result shows that the grain size can be predicted at a lower temperature than 1200 °C. However, the grains show irregular growth at a recrystallization temperature of 1200 °C which leads to a difficult estimation of grain size. It was observed that the variation in values of n and K are associated with the precipitation of the different micro-alloyed elements presented in the stainless steel SS316L. It can be also concluded that the texture plays an important role in the resulting kinetics change.